FAKTOR-FAKTOR YANG MEMPENGARUHI SISA HASIL USAHA (STUDI KASUS PADA KOPERASI KARYAWAN RUMAH SAKIT DEWI SRI KARAWANG) - Ahmad Nawawi; Dian Hakip Nurdiansyah; Suparno Suparno (Jurnal Manajemen Dayasaing, 2019)
This research was conducted at Dewi Sri Karawang Hospital Employee Cooperative. The phenomenon that occurs is the development of the number of members, deposits, and sales in the year 2008-2015 which tends to rise, but the acquisition of remaining unstable business results, even in 2010 suffered losses. The purpose of this study is to determine the effect of Total Members, Deposits, and Sales on the Return of Operating Results in 2008-2015, either partially or simultaneously.      The method used in this research is Quantitative Method. This study uses multiple regression analysis. The data used in this study is secondary data sourced from Annual Financial Report of Cooperative Employees Hospital Dewi Sri Karawang year 2008-2015.      The result of partial research on the number of members to the rest of the business results shows that t count is less than ttable that is 0,742 2,365 which means that the number of members has no effect on the rest of the business result, the saving to the rest of the business result shows that -thount is bigger than -ttabel ie - 0,509 -2,365 which means that the deposit does not affect the rest of the business results, and sales to the rest of the business results show that -thount is greater than -table is -0,286 -2,365 which means that the deposit does not affect the rest of the business results. The results of simultaneous study of the number of members, deposits, and sales shows that F count is smaller than Ftable is 0,213 19,2 which means that the number of members, savings and sales simultaneously (together) has no effect on the rest of the business results.